Improving the methodology for selecting development projects for an industrial enterprise: - MURATOVA, MARINA N.; KAMCHATOVA, EKATERINA YU. (The journal of contemporary issues in business and government, 2020)
The article describes the main elements of the methodology for selecting projects for the development of an industrial enterprise based on a combination of a resource approach and a utility methodology. The main internal indicators of the potential of an industrial enterprise are described, as well as indicators of the potential of the enterprise. On the basis of the system of indicators, a scale of criteria for expert assessment of the enterprise's ability to implement a development project has been developed. The possibility of using the technique for a real industrial enterprise is shown. The main features of the use of the resource approach in the practical activities of industrial enterprises that implement the project approach to the activity development program are considered.